Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am working on a physics task, and reduced it to the following equation for $y$: $$\frac{1}{4y^3}-\frac{2}{(y^2+b^2)^{\frac{3}{2}}}=0$$ I handed it to Mathematica, and it gave me two real solutions, $$y_{1,2} = \pm\frac{b}{\sqrt{3}},$$ along with some complex ones. My question is, how can I see this? I mean, how can I solve such an equation by hand? I tried moving stuff around a bit, but all I found was a sextic equation, which I really didn't feel like approaching. Is there any easier way? Does it lower the hassle, if only real solutions are to be found?

share|improve this question
    
depending on the context there are 6 solutions. (the 3 complex roots of $y^{3}$ for each of the solutions you gave) –  Max Feb 28 at 19:27
    
$y$ is to be interpreted as a radius, so actually the positive solution suffices. –  Pascal Engeler Feb 28 at 19:38
    
Any equation that can be solved by any method can be solved by hand. It just might take a long time. –  AJMansfield Mar 1 at 17:05

3 Answers 3

up vote 13 down vote accepted

Let $x^2=y^2+b^2$. Then $x=\pm2y$ and you find the result

share|improve this answer
2  
This answer gives a "magic" solution, rather than explaining how, which is what the question asked. –  Brian S Feb 28 at 20:24
    
I didn't think it was magic, as it a way to get rid of the cubes. It might be easier to find by clearing fractions and taking the cube root of both sides. –  Ross Millikan Feb 28 at 21:04

First, get rid of the denominators,

$$\begin{align} \frac{1}{4y^3} - \frac{2}{(y^2+b^2)^{3/2}} &= 0\\ \iff \frac{1}{4y^3} &= \frac{2}{(y^2+b^2)^{3/2}}\\ \iff (y^2+b^2)^{3/2} &= 8y^3. \end{align}$$

Then, raise it to the $2/3$-th power to simplify it, introducing a third root of unity,

$$\begin{align} y^2 + b^2 &= 4\rho y^2\\ \iff b^2 &= (4\rho-1)y^2\\ \iff y &= \pm \frac{b}{\sqrt{4\rho-1}}. \end{align}$$

Choosing $\rho = 1$ as the third root of unity yields the two real solutions. $\rho = e^{\pm 2\pi i/3}$ yields non-real solutions.

share|improve this answer

Hint

Rearrange terms, so you can get $$ 8y^3 - \left( \sqrt{y^2+b^2} \right )^3 = 0 $$ Now, use the fact that $a^3 - b^3 = (a-b)(a^2+ab+b^2)$ $$ \left( 2y - \sqrt{y^2+b^2} \right )\left( 4y^2 + 2y \sqrt{y^2+b^2} + y^2 + b^2\right ) = 0 $$ Can you take it from here?

share|improve this answer
2  
$a^3-b^3=(a-b)(a^2+ab+b^2)$ should be more popular indeed! –  Tobias Kienzler Mar 1 at 9:56

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.